QoS Analysis on Video Streaming Service Traffic using OSPF Protocol - Herfiah, Shita; Wulandari, Asri; Meidiansyah, Muhammad Roby (Spektral, 2025)
The demand for video streaming services is constantly increasing, which requires reliable network performance with high Quality of Service (QoS). One of the solutions to improve network performance and guarantee QoS is to implement Multiprotocol Label Switching (MPLS). This research aims to analyze and compare the performance of non-MPLS and MPLS virtual IP networks on video streaming traffic. The research method is conducted through experiments by implementing two routing scenarios, namely non-MPLS networks that implement the Open Shortest Path First (OSPF) protocol and MPLS networks that implement OSPF with the addition of MPLS mechanisms. Tests were conducted using iPerf3 to measure UDP and TCP traffic (upload and download). In addition, QoS parameter analysis was conducted using Wireshark software on video streaming services with 360p, 480p, and 720p resolutions. The results show that MPLS networks can increase throughput, reduce delay and jitter, and reduce packet loss, especially at higher video resolutions. Video with 720p resolution experienced the most significant improvement, namely the throughput value increased by 40.73%, while delay and jitter decreased by 29.40% and 30.28%, and no packet loss was found. This shows that MPLS performance can provide better data transmission for real-time multimedia services such as video streaming.